Game Usage in Pregnant Women at Early Gestation in Japan - Sato, Hiroko; Yasui, Toshiyuki (Global journal of health science, 2022)
BACKGROUND: Gaming addiction is becoming a problem in young women. However, there has been no report on game usage in pregnant women. OBJECTIVE: The aim of this study was to determine the current status of computer game usage and the existence of game addiction and also to determine the associations of game usage time with lifestyle, personal relationships and thoughts about games in pregnant women at early gestation. SUBJECTS & METHODS: We recruited pregnant women who received a pregnancy checkup during the first trimester. We distributed QR codes for the online survey. We conducted a web questionnaire survey including Internet Gaming Disorder Scale (IGDS) in 178 pregnant women. RESULTS: The proportion of women with game usage was 40.4%. The mean game usage time per day was 72.9 minutes. There were no pregnant women whose IGDS score was more than 5 points. We divided 72 participants into three groups by tertile according to game usage time per day: group A (≦ 30 mins), group B (> 30 and ≦ 90 mins) and group C (> 90 mins). There were no significant differences in current smoking, alcohol drinking and daily life behavior among the three groups. There were significant differences in the proportions of women who had difficulty for establishing personal relationships by face-to-face communication and who thought that they might have a game addiction among the three groups. Pregnant women with longer game usage time had a high IGDS score. CONCLUSION: We showed for the first time the proportion of pregnant women who use games in the early period of gestation. Pregnant women with longer game usage time may require careful observation.